2010
DOI: 10.1073/pnas.0913485107
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Parkin requires PINK1 for mitochondrial translocation and ubiquitinates Mitofusin

Abstract: Loss of the E3 ubiquitin ligase Parkin causes early onset Parkinson's disease, a neurodegenerative disorder of unknown etiology. Parkin has been linked to multiple cellular processes including protein degradation, mitochondrial homeostasis, and autophagy; however, its precise role in pathogenesis is unclear. Recent evidence suggests that Parkin is recruited to damaged mitochondria, possibly affecting mitochondrial fission and/or fusion, to mediate their autophagic turnover. The precise mechanism of recruitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
633
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 688 publications
(669 citation statements)
references
References 47 publications
34
633
1
1
Order By: Relevance
“…Next, we explored how Pink1 altered mitochondrial morphology in our model. Previous reports showed that Parkin requires Pink1 for mitochondrial translocation and recruitment 21,22 . Thus, we tested whether Parkin was also recruited to the mitochondria or it was a separate pathway in our signalling axis.…”
Section: Pink1 Inhibits Mitochondrial Fragmentation and Apoptosismentioning
confidence: 97%
“…Next, we explored how Pink1 altered mitochondrial morphology in our model. Previous reports showed that Parkin requires Pink1 for mitochondrial translocation and recruitment 21,22 . Thus, we tested whether Parkin was also recruited to the mitochondria or it was a separate pathway in our signalling axis.…”
Section: Pink1 Inhibits Mitochondrial Fragmentation and Apoptosismentioning
confidence: 97%
“…Subsequently, mitofusin (Mfn; a profusion factor on the outer mitochondrial membrane) is ubiquitinated in a Parkin-dependent manner for degradation by the proteasome (Narendra et al, 2010;Ziviani et al, 2010). Decreasing the levels of Mfn via the PIKN1/Parkin pathway promotes mitochondrial fission, or alternatively inhibits mitochondrial fusion (Poole et al, 2008(Poole et al, , 2010Yang et al, 2008).…”
Section: Mitophagymentioning
confidence: 99%
“…Moreover, PINK1 deficiency or point mutations induce mitochondrial fragmentation in immortal or primary human neuronal cells, indicating that PINK1 and Parkin inhibit mitochondrial fission in human neuronal cells (Exner et al, 2007;Kim et al, 2008a). Recently, several groups reported that the pro-mitochondrial fusion protein Marf and its human homolog, mitofusin (Mfn), are specifically ubiquitinated and degraded by Parkin in both human and Drosophila systems (Gegg et al, 2010;Tanaka et al, 2010;Ziviani et al, 2010). Therefore, the exact molecular mechanisms underlying these different mitochondrial remodeling patterns are expected to be elucidated soon.…”
Section: Parkin Remodels Mitochondria By Ubquitinating Its Mitochondrmentioning
confidence: 99%